Tuberculosis: A persistent unpleasant neighbour of humans. Issue 4 (April 2021) - Seki, Mitsuko; Choi, Hongjo; Kim, Kyungjong; Whang, Jake; Sung, Joohon; Mitarai, Satoshi
Abstract: Mycobacterium tuberculosis, the bacterium that causes tuberculosis, has long been an unpleasant neighbour of humans. Following transmission of the bacterium from patients with active infection, new hosts do not immediately develop symptoms, as M. tuberculosis initially remains quiescent. However, it is eventually triggered, leading to the infection of other individuals. Humans are the exclusive host, and the rapid proliferation of the human population worldwide along with increasing globalisation have contributed to the pathogen's persistence, as have the survival strategies employed by M. tuberculosis, especially its resistance to several antimicrobials. Defeating this enemy will require novel approaches.